Producing Your Own Video Program - Ricky Telg; Peyton Beattie (EDIS)
This 4-page publication of the UF/IFAS Department of Agricultural Education and Communication provides an overview of what you should consider as you create your own video program. Minor revision by Ricky Telg and Peyton Beattie.